2017
DOI: 10.1038/srep43728
|View full text |Cite
|
Sign up to set email alerts
|

HDL Glycoprotein Composition and Site-Specific Glycosylation Differentiates Between Clinical Groups and Affects IL-6 Secretion in Lipopolysaccharide-Stimulated Monocytes

Abstract: The goal of this pilot study was to determine whether HDL glycoprotein composition affects HDL’s immunomodulatory function. HDL were purified from healthy controls (n = 13), subjects with metabolic syndrome (MetS) (n = 13), and diabetic hemodialysis (HD) patients (n = 24). Concentrations of HDL-bound serum amyloid A (SAA), lipopolysaccharide binding protein (LBP), apolipoprotein A-I (ApoA-I), apolipoprotein C-III (ApoC-III), α-1-antitrypsin (A1AT), and α-2-HS-glycoprotein (A2HSG); and the site-specific glycova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 39 publications
5
47
3
Order By: Relevance
“…In our previous study, the glycan ApoC3_74_O_1102, which decreased after FF and increased after Med in this study, was found to be 2-fold higher in HDL compared to plasma, 10 and was elevated in hemodialysis patients, but decreased in MetS patients compared to healthy human controls. 12 Although the glycan ApoC3_74_O_2230, which increased after FF and decreased after Med in this study, was not detected in our previous study, another non-sialylated ApoC-III glycan, ApoC3_74_O_0300, was found to be decreased in hemodialysis patients and elevated in MetS patients. 12 Di-sialylated ApoC-III is enriched in small dense LDL in hemodialysis patients with dyslipidemia, 42 and was found to be reduced across lipoprotein classes in MetS patients.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…In our previous study, the glycan ApoC3_74_O_1102, which decreased after FF and increased after Med in this study, was found to be 2-fold higher in HDL compared to plasma, 10 and was elevated in hemodialysis patients, but decreased in MetS patients compared to healthy human controls. 12 Although the glycan ApoC3_74_O_2230, which increased after FF and decreased after Med in this study, was not detected in our previous study, another non-sialylated ApoC-III glycan, ApoC3_74_O_0300, was found to be decreased in hemodialysis patients and elevated in MetS patients. 12 Di-sialylated ApoC-III is enriched in small dense LDL in hemodialysis patients with dyslipidemia, 42 and was found to be reduced across lipoprotein classes in MetS patients.…”
Section: Discussioncontrasting
confidence: 82%
“…11 Importantly, key HDL proteins are differentially glycosylated in multiple disease states vs. healthy individuals, and site-specific glycosylation of HDL-associated proteins is associated with HDL's immunomodulatory capacity. 12 Apolipoprotein E (ApoE) genotype is one of the most important risk factors for a number of ageassociated diseases, 13 and the single greatest genetic risk factor for Alzheimer's Disease. 14 ApoE is a component of HDL particles that is involved in mediating HDL functional capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Similar differences were found between patients with metabolic syndrome and healthy subjects [27]. Furthermore, HDL glycoprotein composition differentiates between clinical groups, correlating with immunomodulatory capacity of HDL [28].…”
Section: Accepted Manuscriptsupporting
confidence: 66%
“…Given that ABCA1 preferentially effluxes cholesterol to small relative to large HDL [59], such effect should have resulted in the elevated cholesterol efflux capacity of the desialylated particles, which was not the case, suggesting that other factors, including HDL charge, were more important for this functional alteration. We interpret these data to hypothesise that the N-glycome of HDL proteins, including fetuin A, alpha-1-antitripsin, angiotensinogen [26,28,29], LCAT [24] and possibly apoA-I [57,58], can be affected by neuroaminidaseinduced desialylation and that these modifications bear a potential to reduce electronegativity and LCAT activity of HDL to concomitantly contribute to the diminished capacity of HDL to efflux cellular cholesterol via ABCA1, counteracting potentially beneficial effects of the diminished HDL size.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation